Pharmaceutical interventions in the management of tuberculosis in a pneumophtisiology department, Ivory Coast - Abrogoua DP; Kamenan BAT; Ahui BJM; Doffou E (Dove Medical Press, 2016)
Danho Pascal Abrogoua,1 Boua Alexis Thierry Kamenan,1 Brou Jean Marcel Ahui,2 Elisée Doffou3 1Department of Clinical Pharmacy and Therapeutics, Faculty of Pharmaceutical and Biological Sciences, Félix Houphouët-Boigny University, 2Department of Pneumophtisiology, Teaching Hospital of Cocody, 3Department of Pharmacy, Teaching Hospital of Yopougon, Abidjan, Cote d’Ivoire Objectives: This study aims to analyze the profile and relevance of pharmaceutical interventions (PIs) in the management of tuberculosis (TB) at inpatient settings.Patients and methods: Cross-sectional descriptive study conducted from March to December 2014 within the inpatient unit of pneumophtisiology department, Ivory Coast. Information collected was based on the classification of drug-related problems (DRPs) and PIs outlined by the French Society of Clinical Pharmacy. A score was assigned to each PI according to the importance of the potential clinical impact. This score was correlated with the severity of clinical consequences avoided by the intervention. The listing of interventions was made by pneumophtisiology specialists. The score assigned to each intervention ranged from 0 (without clinical impact) to 3 (vital clinical impact). The acceptance rate of interventions by physicians was evaluated.Results: Of 130 patients, 28.5% received PIs. The main reasons for interventions were drug–drug interactions (26.4%), noncompliance with recommendations (24.5%), and adverse effects (24.5%). Antituberculosis drugs were involved in 40.3% of DRPs. Interventions were predominantly proposals for monitoring treatment effectiveness and safety parameters (52.7%) followed by proposals of therapeutic choice (28.1%). All interventions were accepted by the physicians. Most interventions (59.6%) were listed as interventions with significant clinical impact.Conclusion: The presence of a pharmacist at inpatient setting has contributed to the prevention and resolution of problems related to the pharmacotherapeutic management of TB. Pharmacists can position themselves as major players in the therapeutic management of TB inpatient in resource-limited setting. Keywords: tuberculosis, drug-related problem, pharmaceutical intervention, relevance, clinical impact, Ivory Coast